Pengaruh Globalisasi terhadap Kebijakan Luar Negeri Indonesia di Era Digital - Fitri Yanti (Jurnal Ilmu Hubungan Internasional LINO, 2025)
Globalization and advancements in digital technology have transformed international relations, including Indonesia’s foreign policy. This study analyzes how globalization, accelerated by digital technology, impacts Indonesia's foreign policy. The primary focus is on the role of digital technology in Indonesia's diplomacy and the challenges faced, such as cyber threats and disinformation. Using a qualitative approach, this research identifies that although Indonesia has utilized digital diplomacy to strengthen its international image, foreign policy still needs to be strengthened with policies more adaptive to technological and globalization changes. The study also offers recommendations to enhance cybersecurity, improve diplomat training, and develop policies responsive to global dynamics.